Remote magnetic‐guided ablation for three origins of idiopathic ventricular arrhythmias with right bundle branch block and superior axis. Issue 3 (20th January 2021) - Li, Xiang; Shang, Wentao; Zhang, Ning; Xie, Yun; Wei, Yue; Lin, Changjian; Ling, Tianyou; Chen, Kang; Pan, Wenqi; Wu, Liqun; Bao, Yangyang; Jin, Qi
Abstract: Background: Idiopathic ventricular arrhythmias (IVAs) with right bundle branch block (RBBB) and superior axis commonly originate from posterior mitral annulus (PMA), the left ventricular (LV) posterior fascicle (LPF), and the LV posterior papillary muscles (PPM). Hypothesis: Remote magnetic navigation (RMN)‐guided ablation might be safe and effective for these three origins of IVAs. Methods: Thirty consecutive IVA patients with RBBB and superior axis (11 MPA‐IVAs, 11 LPF‐IVAs, and 8 PPM‐IVAs) were included in this study. Electrical mapping and ablation with RMN were performed in the LV through a trans‐septal approach. Navigation index, defined as the ratio of total radiofrequency (RF) time and the time from first burn to last burn, was used to determine the efficiency of RMN‐guided ablation. Results: The overall acute success rate was achieved in 93% (PMA, 100%; LPF, 91%; PPM, 88%; p > 0.05). No complication occurred in this study. The procedure time of PPM‐IVAs group was 34 and 14 min longer when compared with MPA‐IVAs and LPF‐IVAs group, respectively, without an increase of X‐ray time. The mean navigation index was 0.45 ± 0.20. The PPM‐IVAs group had an underperforming navigation index value (0.29 ± 0.11) ( p < 0.01), as longer RF time was required in the PPM‐IVAs group. Conclusions: RMN‐guided ablation can achieve a high acute success rate for IVAs with RBBB and superior axis. The lower navigation index for PPM‐IVAs indicated that increasing the RF time and improving the catheter contact should be considered when using RMN.